A composite nanofiltration membrane with a catalytic intermediate layer and its preparation method and application
By setting up a catalytic intermediate layer in the nanofiltration membrane, using aminopyridine catalyst and anchoring compounds to improve the interfacial polymerization activity, the problem of poor separation effect of existing nanofiltration membranes in strong acid and strong alkali environments is solved, and high throughput is achieved and high intercept rate separation effect.
Patent Information
- Application Number
- CN202211148335.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-09-20
AI Technical Summary
The existing nanofiltration membranes have poor separation effect in strong acid, strong alkali, and organic solvent environments, and the low-active interface polymerization monomer results in low self-inhibitability of reaction and low permeability selectivity.
Using a composite nanofiltration membrane with a catalytic intermediate layer, the catalyst intermediate layer material includes an aminopyridine catalyst and an anchoring compound, which improves the reactivity of the interface polymerization monomer and enhances the self-inhibitability of the interface polymerization reaction.
High throughput and high salt ion retention rate are achieved, separation efficiency is improved, the resistance of water passing through the separation layer is reduced, and the stability of interfacial polymerization reaction is enhanced.
Smart Images

Figure CN115430296B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a composite nanofiltration membrane with a catalytic intermediate layer and a preparation method and application thereof. Background Art
[0002] The continuous development of industry has aggravated the global water shortage and water pollution. Compared with high-energy-consuming treatment processes such as adsorption, distillation, and electrodialysis, pressure-driven membrane separation technology has lower energy consumption and higher separation efficiency. In membrane separation technology, nanofiltration membranes have excellent effects in the selective separation of small-molecule organic matter and multivalent salt ions with a molecular weight cutoff of 200-2000Da, and have been widely used in drinking water treatment, small-molecule desalination, bioproduct decolorization, and wastewater resource utilization.
[0003] At present, nanofiltration membranes are mainly thin film composite membranes, which have a structure of a porous support membrane and an active separation layer formed by interfacial polymerization of polyamines and polyacyl chlorides on the surface of the support layer. As industrial separation systems become more diversified and complex, the requirements for the permeability selectivity of nanofiltration membranes are further improved. At present, commercial nanofiltration membranes are mainly based on polypiperazineamide composite membranes prepared from piperazine and 1,3,5-benzenetricarboxylic acid chloride, and the separation efficiency is still not high. In addition, for special nanofiltration membranes used in strong acid, strong alkali, and organic solvent environments, the low monomer reaction activity further hinders the rapid progress of the interfacial polymerization reaction, and the separation layer formed is thicker and the separation effect is poor.
[0004] The permeability selectivity of nanofiltration membranes is fundamentally determined by the self-inhibition of interfacial polymerization reactions. According to the literature (Interfacial Polymerization: From Chemistry to Functional Materials, Angewandte Chemie, 2020, 59, 21840.), interfacial polymerization reactions with low self-inhibition will limit the formation of a uniform separation layer and reduce the permeability separation performance of the composite membrane. Regulating the interfacial polymerization reaction at the water-oil phase interface is an effective method to improve the self-inhibition of the reaction and improve the permeability selectivity of the composite membrane. At present, most methods mainly regulate the diffusion behavior of the water phase monomer to reduce the disordered diffusion of the reaction monomer at the phase interface, but the effect is very limited for low-activity monomers.
[0005] For example, CN112808021A discloses a method for preparing a polyamide composite membrane using a novel aqueous phase system, wherein the composite membrane uses anionic surfactants and cationic surfactants as additives for a polyamine aqueous phase solution, thereby improving the dispersion uniformity of aqueous phase monomers and promoting the uniform diffusion of aqueous phase monomers at the phase interface, and the prepared composite membrane has an improved flux and retention rate. However, the composite membrane has high requirements on the dispersion state of the surfactant in the solution and the stability of the phase interface.
[0006] CN107837689A discloses a method for preparing a composite nanofiltration membrane with an ultra-thin separation layer, wherein the thickness of the separation layer is reduced and the permeability is significantly improved by adding polyol macromolecules to the aqueous phase solution to limit the diffusion of monomers in the main solution and the phase interface. However, the hindered interfacial polymerization reaction greatly increases the requirements for the reactivity of the aqueous phase monomers.
[0007] CN112892225A discloses a method for preparing a thin-layer composite membrane by electrospraying. The aqueous and oily phase solutions are spread on the surface of a porous support membrane in the form of microdroplets by electrospraying technology, thereby improving the problem of heterogeneous distribution of the interfacial polymerization composite membrane in space and chemical composition. The permeability selectivity of the prepared composite membrane is improved. However, the composite membrane has high requirements for equipment conditions, which restricts its industrial promotion.
[0008] Therefore, it is a technical problem to be urgently solved in this field to develop a nanofiltration membrane with high flux and high salt ion retention rate for water, a composite nanofiltration membrane with a simple preparation method and adjustable separation capacity, and a composite nanofiltration membrane with high water flux and retention rate using low-activity interfacial polymerization monomers. Summary of the invention
[0009] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite nanofiltration membrane with a catalytic intermediate layer, and a preparation method and application thereof. The composite nanofiltration membrane is provided with a catalytic intermediate layer, and the material of the catalytic intermediate layer includes an aminopyridine catalyst and an anchoring compound, which not only makes the composite nanofiltration membrane have high flux characteristics, but also ensures a high retention rate of divalent inorganic salt ions; and the catalytic intermediate layer can also improve the reaction activity of the interfacial polymerization monomer, broaden the scope of monomer use, and make low-activity monomers also have a higher water flux and retention rate; at the same time, it reduces the disordered diffusion of reactants at the phase interface, enhances the self-inhibition of the interfacial polymerization reaction, and can effectively solve the problems of low permeability flux of nanofiltration membranes, poor stability in large-scale production, and limited use conditions in the prior art.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a composite nanofiltration membrane having a catalytic intermediate layer, the composite nanofiltration membrane comprising a support layer, a catalytic intermediate layer and an active separation layer arranged in sequence; the material of the catalytic intermediate layer comprises an aminopyridine catalyst and an anchoring compound; the anchoring compound comprises at least one of polyphenol, polycellulose, polydopamine, polyacrylic acid, polyurethane, polyvinyl alcohol, polylactic acid, a metal organic framework material or a covalent organic framework material.
[0012] In the present invention, the catalytic intermediate layer can reduce the energy barrier of the interfacial polymerization reaction by forming active intermediates with the organic phase monomers near the phase interface, improve the activity of the reaction monomers, and enhance the self-inhibition of the interfacial polymerization reaction. In addition, due to the selection of anchoring compounds, the diffusion loss of catalyst molecules can be avoided, and at the same time, the surface structure of the support layer is optimized, and the uniform adsorption and release of the aqueous phase monomers are promoted to form an active separation layer with a more uniform structure. The stronger the self-inhibition of the interfacial polymerization reaction, the more uniform the structure of the active separation layer, the higher the flux of the prepared composite membrane, and the better the desalination effect.
[0013] Preferably, in parts by weight, the material of the catalytic intermediate layer includes 0.001 to 10 parts of aminopyridine catalyst, for example, 0.002 parts, 0.004 parts, 0.006 parts, 0.008 parts, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 4 parts, 6 parts, 8 parts, etc.
[0014] Preferably, the aminopyridine catalyst comprises nanoparticles containing aminopyridine groups.
[0015] Preferably, the raw materials of the nanoparticles containing aminopyridine groups include 4-aminopyridine and a nanoparticle precursor.
[0016] Preferably, the molar ratio of the nanoparticle precursor to 4-aminopyridine is 1:(1-2), for example, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, etc.
[0017] Preferably, the nanoparticles containing aminopyridine groups include organic nanoparticles containing aminopyridine groups and / or inorganic nanoparticles containing aminopyridine groups.
[0018] In the present invention, the morphology of the nanoparticles containing aminopyridine groups is not excessively limited, including but not limited to at least one of porous flaky inorganic aminopyridine nanoparticles, non-porous flaky inorganic aminopyridine nanoparticles, porous non-flaky inorganic aminopyridine nanoparticles, non-porous non-flaky inorganic aminopyridine nanoparticles, porous flaky organic aminopyridine nanoparticles, non-porous flaky organic aminopyridine nanoparticles, porous non-flaky organic aminopyridine nanoparticles or non-porous non-flaky organic aminopyridine nanoparticles.
[0019] Preferably, the nanoparticles containing aminopyridine groups include aminopyridine carbon quantum dots and / or aminopyridine graphene.
[0020] Preferably, in parts by weight, the material of the catalytic intermediate layer includes 0.01 to 0.1 parts of the anchor compound, for example, 0.015 parts, 0.02 parts, 0.025 parts, 0.03 parts, 0.035 parts, 0.04 parts, 0.045 parts, 0.05 parts, 0.055 parts, 0.06 parts, 0.065 parts, 0.07 parts, 0.075 parts, 0.08 parts, 0.085 parts, 0.09 parts, 0.095 parts, etc.
[0021] Preferably, the material of the active separation layer includes an interfacial polymer formed by water-phase reactants and oil-phase reactants.
[0022] Preferably, the aqueous phase reactants include monomers containing reactive groups.
[0023] Preferably, the functionality of the monomer containing a reactive group is ≥ 2, for example, it may be 2, 3, 4, etc.
[0024] Preferably, the reactive group comprises at least one of an amino group, a hydroxyl group or a sulfonamide group.
[0025] Preferably, the monomer containing a reactive group comprises at least one of m-phenylenediamine, piperazine, resorcinol, 3-aminobenzenesulfonamide, polyethyleneimine or triethylenetetramine.
[0026] Preferably, the aqueous phase reactant includes 0.01 to 10 parts of monomers containing reactive groups, in parts by weight, for example, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, etc.
[0027] Preferably, the mass ratio of the monomer containing reactive groups to the aminopyridine catalyst is (1-10):1, for example, it can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, etc.
[0028] Preferably, the aqueous phase reactant further includes 0.01 to 15 parts of additives, by weight, for example, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, etc.
[0029] Preferably, the additive comprises an acid binder and / or a surfactant.
[0030] Preferably, the acid binding agent comprises at least one of triethylamine, sodium hydroxide, potassium hydroxide or sodium carbonate.
[0031] Preferably, the content of the acid binding agent in the additive is 0.01 to 10 parts by weight, for example, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 2 parts, 4 parts, 6 parts, 8 parts, etc.
[0032] Preferably, the content of the surfactant in the additive is 0.01 to 5 parts by weight, for example, 0.02 parts, 0.04 parts, 0.06 parts, 0.08 parts, 0.1 parts, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 2 parts, 4 parts, etc.
[0033] Preferably, the surfactant includes at least one of anionic surfactants, cationic surfactants or zwitterionic surfactants.
[0034] Preferably, the oil phase reactant comprises an acyl halide compound.
[0035] Preferably, the acyl halide compound comprises an aliphatic acyl halide compound and / or an aromatic acyl halide compound.
[0036] Preferably, the functionality of the acyl halide compound is ≥ 2, for example, it may be 2, 3, 4, etc.
[0037] Preferably, the acyl halide compound comprises an acyl chloride compound and / or an acyl bromide compound.
[0038] Preferably, the acyl halide compound includes at least one of 1,3,5-benzenetricarboxylic acid chloride, 2,6-naphthalene dicarboxylic acid chloride, terephthaloyl chloride, isophthaloyl chloride or phthaloyl chloride.
[0039] Preferably, the oil phase reactant includes 0.01 to 10 parts of acyl halide compounds, for example, 0.02, 0.04, 0.06, 0.08, 0.1, 0.2, 0.4, 0.6, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, etc., by weight.
[0040] Preferably, the support layer comprises a porous support layer.
[0041] Preferably, the support layer includes at least one of a polysulfone support layer, a polyethersulfone support layer, a polyethylene support layer, a polyamide support layer, a polyimide support layer, a polytetrafluoroethylene support layer, a polyvinylidene fluoride support layer, a polyacrylonitrile support layer or a polyetherimide support layer.
[0042] In a second aspect, the present invention provides a method for preparing the composite nanofiltration membrane according to the first aspect, the preparation method comprising:
[0043] The support layer, the catalytic intermediate layer and the active separation layer are stacked in sequence to obtain the composite nanofiltration membrane.
[0044] Preferably, the method for preparing the catalytic intermediate layer comprises:
[0045] The aminopyridine catalyst and the anchor compound are mixed with a solvent to obtain an anchor coating solution containing the aminopyridine catalyst; the anchor coating solution is coated on the surface of the support layer to obtain the catalytic intermediate layer.
[0046] In the present invention, the solvent includes water.
[0047] Preferably, the step of washing the support layer is further included before coating the surface of the support layer.
[0048] Preferably, the washing solvent comprises ethanol and / or water.
[0049] When the washing solvent in the present invention is an aqueous solution of ethanol, the mass concentration is 10-99%, for example, 10%, 20%, 30%, 50%, 80%, etc.
[0050] Preferably, the coating method includes at least one of dipping, spin coating or spray coating.
[0051] Preferably, the immersion time is 20 to 30 hours, for example, 22 hours, 24 hours, 26 hours, 28 hours, etc.
[0052] In the present invention, after the immersion for 20 to 30 hours, the method further comprises rotating at 1000 to 2000 rpm (for example, 1200 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1800 rpm, etc.) for 10 to 20 s (for example, 12 s, 14 s, 16 s, 18 s).
[0053] Preferably, the method for preparing the active separation layer comprises:
[0054] The surface of the catalytic intermediate layer away from the supporting layer is treated in sequence with a water phase reactant solution and an oil phase reactant solution to perform an interfacial polymerization reaction, thereby obtaining the active separation layer.
[0055] In the present invention, the solvent in the aqueous phase reactant solution includes water.
[0056] Preferably, the water content in the aqueous phase reactant solution is 75 to 99.999 parts by weight, for example, it can be 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 96 parts, 98 parts, etc.
[0057] Preferably, the aqueous phase reactant also includes an acid binding agent and / or an additive.
[0058] Preferably, the method of treating comprises impregnation.
[0059] Preferably, the time for treating the surface of the catalytic intermediate layer away from the support layer with the aqueous reactant solution is 5 to 15 minutes, for example, 6 minutes, 8 minutes, 10 minutes, 12 minutes, 14 minutes, etc.
[0060] Preferably, the time for treating the surface of the catalytic intermediate layer away from the supporting layer with the oil phase reactant solution is 20 to 40 seconds, for example, 22 seconds, 24 seconds, 26 seconds, 28 seconds, 30 seconds, 32 seconds, 34 seconds, 36 seconds, 38 seconds, etc.
[0061] In the present invention, the solvent in the oil phase reactant solution includes at least one of n-hexane, heptane, dodecane, petroleum ether, toluene, chloroform, cyclohexane, ethyl acetate or xylene.
[0062] Preferably, the content of the solvent in the oil phase reactant solution is 90 to 99.999 parts by weight, for example, 91 parts, 92 parts, 94 parts, 96 parts, 98 parts, etc.
[0063] Preferably, after obtaining the active separation layer, solvent immersion treatment and / or heat treatment is further performed.
[0064] Preferably, the solvent in the solvent soaking treatment includes at least one of water, hydrochloric acid, sodium hydroxide, n-hexane, ethanol, triethylamine, benzenesulfonic acid, formamide or ethanolamine.
[0065] Preferably, the solvent immersion treatment time is 1 to 10 minutes, for example, 2 minutes, 4 minutes, 6 minutes, 8 minutes, etc.
[0066] Preferably, the heat treatment temperature is 40-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, etc.
[0067] Preferably, the heat treatment time is 1 to 30 min, for example, 2 min, 4 min, 6 min, 8 min, 10 min, 14 min, 16 min, 18 min, 20 min, 24 min, 26 min, 28 min, etc.
[0068] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0069] (1) mixing an aminopyridine catalyst and an anchor compound with a solvent to obtain an anchor coating solution containing an aminopyridine catalyst; coating the anchor coating solution on the surface of the washed support layer to obtain the catalytic intermediate layer;
[0070] (2) After the surface of the catalytic intermediate layer away from the support layer is impregnated with an aqueous phase reactant solution for 5 to 15 minutes, the surface of the catalytic intermediate layer away from the support layer is impregnated with an oil phase reactant solution for 20 to 40 seconds to perform an interfacial polymerization reaction, and then the mixture is immersed in a solvent for 1 to 10 minutes and treated at 40 to 100° C. for 20 to 40 seconds to obtain the composite nanofiltration membrane.
[0071] In a third aspect, the present invention provides a desalination nanofiltration membrane, wherein the desalination nanofiltration membrane comprises the composite nanofiltration membrane as described in the first aspect.
[0072] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] (1) The composite nanofiltration membrane provided by the present invention adopts a catalytic intermediate layer to improve the monomer reaction activity and broaden the application range of low-activity monomers. At the same time, the aminopyridine catalyst is fixed in the intermediate layer to limit the disordered diffusion of the catalytic intermediate, enhance the phase interface stability, and improve the self-inhibition of the interfacial polymerization reaction, thereby obtaining a high-flux composite nanofiltration membrane with a uniform active separation layer structure, reducing the resistance of water passing through the separation layer, thereby improving the separation efficiency in the water treatment process;
[0075] (2) The composite nanofiltration membrane provided by the present invention has a 15Lm -2 h -1 bar -1 The water flux is above 1000ppm, and the retention rate of divalent sulfate ions with a concentration of 1000ppm is above 90%. This high-flux, low-energy composite nanofiltration membrane has great application potential in desalination and wastewater treatment.
[0076] (3) The composite nanofiltration membrane provided by the present invention has a simple preparation method, good reproducibility, good universality, and can control the content of aminopyridine catalyst in the catalytic intermediate layer according to different processing requirements to obtain a composite membrane with different separation performances. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 A schematic diagram of the structure of a composite nanofiltration membrane with a catalytic intermediate layer provided by the present invention;
[0078] Among them, 1-porous support membrane; 2-catalytic intermediate layer; 3-active separation layer. DETAILED DESCRIPTION
[0079] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0080] Unless otherwise specified, the materials used in all embodiments and comparative examples of the present invention are as follows:
[0081] ZIF-8 metal organic framework material: zinc nitrate hexahydrate (purchased from Shanghai Aladdin Co., Ltd., purity 98%) was weighed and dissolved in a 2-methylimidazole (purchased from Shanghai Aladdin Co., Ltd., purity 98%) aqueous solution to obtain a ZIF-8 metal organic framework material solution;
[0082] Polydopamine: dopamine hydrochloride (purchased from Shanghai Aladdin Co., Ltd., purity 98%) was weighed and dissolved in a Tris buffer solution (pH 8.5, 50 mM) to obtain the polydopamine solution;
[0083] Aminopyridine carbon quantum dots: The aminopyridine carbon quantum dots were prepared by microwave heating, 4-aminopyridine (purchased from Shanghai Aladdin Co., Ltd., with a purity of 98%) and anhydrous citric acid (purchased from Shanghai Aladdin Co., Ltd., with a purity of 97%) were weighed and dissolved in water, and the product solution was diluted and neutralized after microwave heating, and the aminopyridine carbon quantum dots were obtained by dialysis purification and freeze drying;
[0084] Aminopyridine graphene: The aminopyridine graphene is prepared by carbodiimide (EDC-NHS) grafting method, 4-aminopyridine (purchased from Shanghai Aladdin Co., Ltd., purity 98%) is weighed and dissolved in graphene oxide dispersion (purchased from Shanghai Aladdin Co., Ltd.), 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide iodide (purchased from Shanghai Aladdin Co., Ltd., purity 98%) and N-hydroxysuccinimide (purchased from Shanghai Aladdin Co., Ltd., purity 98%) are added, stirred at room temperature, purified by dialysis and freeze-dried to obtain the aminopyridine graphene;
[0085] Aminated carbon quantum dots: The aminated carbon quantum dots are prepared by the method disclosed in patent document CN110157422A;
[0086] Activated carbon quantum dots: prepare a deionized water suspension of carbon quantum dots, add sodium hydroxide to adjust the pH, then add 2-chloro-1-methyl iodine pyridine (CMPI) to activate the carbon quantum dots, and stir for half an hour to obtain the activated carbon quantum dots; the molar ratio of the carbon quantum dots to the CMPI is 1:1.5;
[0087] Polyethersulfone porous support layer: The polyethersulfone porous support layer (MQ, molecular weight cut-off 50 kDa) was purchased from Xingda (Taizhou) Membrane Technology Co., Ltd.;
[0088] In the present invention, the amounts of aminopyridine catalyst and anchor compound used in the examples and comparative examples refer to the amounts of effective ingredients excluding the solvent;
[0089] In the preparation method, the total amount of the anchor coating aqueous solution, the aqueous phase reactant solution and the oil phase reactant solution is 100 parts, that is, when each component is dissolved in the solvent respectively, the amount of solvent used makes the total amount 100 parts.
[0090] Example 1
[0091] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.1 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 1 part of 3-aminobenzenesulfonamide, 2 parts of triethylamine and 1 part of sodium dodecyl sulfate; the oil phase reactants comprise 0.5 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0092] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, which specifically comprises the following steps:
[0093] (1) The polyethersulfone porous support membrane was fully washed with an ethanol aqueous solution with a mass concentration of 50%, and then placed in an aqueous solution of an anchor coating containing aminopyridine carbon quantum dots and ZIF-8 metal organic framework materials, and immersed on one side for 24 hours to obtain a catalytic intermediate layer;
[0094] (2) The catalytic intermediate layer obtained in step (1) is immersed in an aqueous phase reactant solution for 8 minutes, and then immersed in a n-hexane solution of 1,3,5-benzenetricarboxylic acid chloride for 30 seconds to perform an interfacial polymerization reaction to obtain an active separation layer; then, the mixture is immersed in a pure water solvent for 1 minute, heat-treated at 40° C. for 5 minutes, and then washed with pure water to obtain the composite nanofiltration membrane.
[0095] Example 2
[0096] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.1 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 1 part of 3-aminobenzenesulfonamide, 2 parts of triethylamine and 1 part of sodium dodecyl sulfate; the oil phase reactants comprise 0.5 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.2.
[0097] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, which specifically comprises the following steps:
[0098] (1) The polyethersulfone porous support membrane was fully washed with an ethanol aqueous solution with a mass concentration of 50%, and then placed in an aqueous solution of an anchor coating containing aminopyridine carbon quantum dots and ZIF-8 metal organic framework materials, and immersed on one side for 24 hours, and then rotated at a speed of 1500 rpm for 15 seconds to obtain a catalytic intermediate layer;
[0099] (2) The catalytic intermediate layer obtained in step (1) is immersed in an aqueous phase reactant solution for 8 minutes, and then immersed in a n-hexane solution of 1,3,5-benzenetricarboxylic acid chloride for 30 seconds to perform an interfacial polymerization reaction to obtain an active separation layer; then, the mixture is immersed in a pure water solvent for 1 minute, heat-treated at 40° C. for 5 minutes, and then washed with pure water to obtain the composite nanofiltration membrane.
[0100] Example 3
[0101] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.5 parts of aminopyridine carbon quantum dots and 0.08 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 4 parts of 3-aminobenzenesulfonamide, 4 parts of triethylamine and 2 parts of sodium dodecyl sulfate; the oil phase reactants comprise 2 parts of 1,3,5-benzenetricarboyl chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.8.
[0102] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, which specifically comprises the following steps:
[0103] (1) The polyethersulfone porous support membrane was fully washed with an ethanol aqueous solution with a mass concentration of 50%, and then placed in an aqueous solution of an anchor coating containing aminopyridine carbon quantum dots and ZIF-8 metal organic framework materials, and immersed on one side for 24 hours to obtain a catalytic intermediate layer;
[0104] (2) The catalytic intermediate layer obtained in step (1) is immersed in an aqueous phase reactant solution for 8 minutes, and then immersed in a n-hexane solution of 1,3,5-benzenetricarboxylic acid chloride for 30 seconds to perform an interfacial polymerization reaction to obtain an active separation layer; then, the mixture is immersed in a pure water solvent for 1 minute, heat-treated at 40° C. for 5 minutes, and then washed with pure water to obtain the composite nanofiltration membrane.
[0105] Example 4
[0106] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.1 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 1 part of piperazine, 2 parts of potassium hydroxide and 1 part of sodium dodecylbenzene sulfonate; the oil phase reactants comprise 0.5 parts of isophthaloyl chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0107] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, and the specific steps are the same as those in Embodiment 1.
[0108] Example 5
[0109] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.1 parts of aminopyridine graphene and 0.05 parts of polydopamine; the active separation layer comprises an interfacial polymer formed by water-phase reactants and oil-phase reactants; in parts by weight, the water-phase reactants comprise 1 part of 3-aminobenzenesulfonamide, 2 parts of triethylamine and 1 part of sodium dodecyl sulfate; the oil-phase reactants comprise 0.5 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of graphene oxide to 4-aminopyridine in the raw material of the aminopyridine graphene is 1:1.5.
[0110] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, and the specific steps are the same as those in Embodiment 1.
[0111] Example 6
[0112] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.1 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 1 part of 3-aminobenzenesulfonamide, 2 parts of triethylamine and 1 part of sodium dodecyl sulfate; the oil phase reactants comprise 0.5 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0113] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, which differs from Embodiment 1 only in that the pure water solvent immersion treatment in step (2) is replaced by n-hexane solvent immersion treatment, and the other steps and parameters are the same as those in Embodiment 1.
[0114] Example 7
[0115] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 0.001 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 0.01 parts of 3-aminobenzenesulfonamide; the oil phase reactants comprise 0.001 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0116] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, and the specific steps and parameters are the same as those in Embodiment 1.
[0117] Example 8
[0118] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 1 part of aminopyridine carbon quantum dots and 0.03 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by aqueous phase reactants and oil phase reactants; in parts by weight, the aqueous phase reactants comprise 6 parts of 3-aminobenzenesulfonamide, 6 parts of triethylamine and 3 parts of sodium dodecyl sulfate; the oil phase reactants comprise 4 parts of 1,3,5-benzenetricarboyl chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0119] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, and the specific steps and parameters are the same as those in Embodiment 1.
[0120] Example 9
[0121] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 5 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by water phase reactants and oil phase reactants; in parts by weight, the water phase reactants comprise 5 parts of 3-aminobenzenesulfonamide, 5 parts of triethylamine and 2.5 parts of sodium dodecyl sulfate; the oil phase reactants comprise 5 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0122] This embodiment provides a method for preparing the composite nanofiltration membrane having a catalytic intermediate layer, which specifically comprises the following steps:
[0123] (1) The polyethersulfone porous support membrane was fully washed with an ethanol aqueous solution with a mass concentration of 50%, and then placed in an aqueous solution of an anchor coating containing aminopyridine carbon quantum dots and ZIF-8 metal organic framework materials, and immersed on one side for 24 hours to obtain a catalytic intermediate layer;
[0124] (2) The catalytic intermediate layer obtained in step (1) is immersed in an aqueous phase reactant solution for 8 minutes, and then immersed in a n-hexane solution of 1,3,5-benzenetricarboxylic acid chloride for 30 seconds to perform an interfacial polymerization reaction to obtain an active separation layer; then, the mixture is immersed in a pure water solvent for 1 minute, heat-treated at 70° C. for 15 minutes, and then washed with pure water to obtain the composite nanofiltration membrane.
[0125] Example 10
[0126] The present embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, the composite nanofiltration membrane comprising a polyethersulfone porous support layer, a catalytic intermediate layer and an active separation layer stacked in sequence; in parts by weight, the material of the catalytic intermediate layer comprises 10 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; the active separation layer comprises an interfacial polymer formed by water phase reactants and oil phase reactants; in parts by weight, the water phase reactants comprise 10 parts of 3-aminobenzenesulfonamide, 10 parts of triethylamine and 5 parts of sodium dodecyl sulfate; the oil phase reactants comprise 10 parts of 1,3,5-benzenetricarboxylic acid chloride; the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw materials of the aminopyridine carbon quantum dots is 1:1.5.
[0127] This embodiment provides a method for preparing the composite nanofiltration membrane with a catalytic intermediate layer, which specifically comprises the following steps:
[0128] (1) The polyethersulfone porous support membrane was fully washed with an ethanol aqueous solution with a mass concentration of 50%, and then placed in an aqueous solution of an anchor coating containing aminopyridine carbon quantum dots and ZIF-8 metal organic framework materials, and immersed on one side for 24 hours to obtain a catalytic intermediate layer;
[0129] (2) The catalytic intermediate layer obtained in step (1) is immersed in an aqueous phase reactant solution for 8 minutes, and then immersed in a n-hexane solution of 1,3,5-benzenetricarboxylic acid chloride for 30 seconds to perform an interfacial polymerization reaction to obtain an active separation layer; then, it is immersed in a pure water solvent for 10 minutes, heat-treated at 100° C. for 30 minutes, and washed with pure water to obtain the composite nanofiltration membrane.
[0130] Embodiment 11
[0131] This embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, which is different from Example 1 only in that the amount of the ZIF-8 metal organic framework material is 0.2 parts, and the other components, amounts, structures and preparation methods are the same as those in Example 1.
[0132] Example 12
[0133] This embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Embodiment 1 only in that the total amount of aminopyridine carbon quantum dots and 3-aminobenzenesulfonamide remains unchanged, with a mass ratio of 15:1, and other components, dosage, structure and preparation method are the same as those in Embodiment 1.
[0134] Embodiment 13
[0135] This embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Embodiment 1 only in that the aminopyridine carbon quantum dots are replaced with an equal amount of 4-aminopyridine, and the other components, amounts, structures and preparation methods are the same as those in Embodiment 1.
[0136] Embodiment 14
[0137] This embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Embodiment 1 only in that the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw material of the aminopyridine carbon quantum dots is 1:0.5, and the other components, dosage, structure and preparation method are the same as those in Embodiment 1.
[0138] Embodiment 15
[0139] This embodiment provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Embodiment 1 only in that the molar ratio of anhydrous citric acid to 4-aminopyridine in the raw material of the aminopyridine carbon quantum dots is 1:2.5, and the other components, dosage, structure and preparation method are the same as those in Embodiment 1.
[0140] Comparative Example 1
[0141] This comparative example provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Example 1 only in that the aminopyridine carbon quantum dots are replaced by amino carbon quantum dots, and the other components, dosage, structure and preparation method are the same as those in Example 1.
[0142] Comparative Example 2
[0143] This comparative example provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Example 1 only in that the aminopyridine carbon quantum dots are replaced by carbon quantum dots activated by 2-chloro-1-methyl-iodopyridine, and the other components, dosage, structure and preparation method are the same as those in Example 1.
[0144] Comparative Example 3
[0145] This comparative example provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Example 1 only in that the material of the catalytic intermediate layer does not contain aminopyridine carbon quantum dots, and the other components, dosage, structure and preparation method are the same as those in Example 1.
[0146] Comparative Example 4
[0147] This comparative example provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Example 1 only in that the material of the catalytic intermediate layer does not contain ZIF-8 metal organic framework material, and other components, dosage, structure and preparation method are the same as those in Example 1.
[0148] Comparative Example 5
[0149] This comparative example provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Example 1 only in that the composite nanofiltration membrane does not have a catalytic intermediate layer; in the preparation method, step (1) is not performed, and other components, amounts and preparation methods are the same as those in Example 1.
[0150] Comparative Example 6
[0151] This comparative example provides a composite nanofiltration membrane with a catalytic intermediate layer, which differs from Example 1 only in that the composite nanofiltration membrane does not have a catalytic intermediate layer; the aqueous phase reactant also includes 0.1 parts of aminopyridine carbon quantum dots and 0.05 parts of ZIF-8 metal organic framework material; in the preparation method, step (1) is not performed, and the other components, amounts and preparation methods are the same as those in Example 1.
[0152] Performance Testing
[0153] The composite nanofiltration membranes provided in Test Examples 1 to 15 and Comparative Examples 1 to 6 were subjected to selectivity tests and roughness tests on water and inorganic salts:
[0154] (1) Test of water flux of composite nanofiltration membrane and its retention performance for inorganic salts: The test was carried out in a high-pressure cross-flow device (FloMem-0010-HP, purchased from Xiamen Shida Membrane Technology Co., Ltd.). The effective volume of the feed tank was 2.5 L, and the effective membrane area was 16 cm 2 The filtration process was carried out in full circulation mode at a cross-flow rate of 7 L / min. The water flux was calculated according to the following formula:
[0155]
[0156] Where P is the permeation flux (Lm -2 h -1 bar -1 );V p is the volume of permeate collected in time t (L); Am is the effective membrane area (m 2 ), t is the running time (h), and TMP is the transmembrane pressure (bar).
[0157] The retention rate of inorganic salts is calculated according to the following formula:
[0158]
[0159] Among them C p and C r Represents the concentration of solute in the permeate and retentate respectively: For inorganic salt solution, the concentration ratio can be replaced by the conductivity ratio. The above test was carried out at 25℃ and the flow rate was 79.6Lm -2 , the concentration of inorganic salt solution is 1000ppm.
[0160] (2) Roughness test:
[0161] The surface roughness of the membrane was analyzed by atomic force microscopy. The membrane sample was cut into 1 cm × 1 cm size and placed on a glass slide. The tapping mode was used at room temperature to measure the surface roughness of the membrane. 2 The roughness of the membrane surface of different sizes was characterized, and 3-5 different positions were randomly selected for measurement; the root mean square roughness (nm) of the membrane surface was recorded.
[0162] The specific test results are shown in Table 1:
[0163] Table 1
[0164]
[0165]
[0166] As can be seen from the above table, the composite nanofiltration membrane provided by the present invention, by providing a catalytic intermediate layer, and the material of the catalyst intermediate layer includes an aminopyridine catalyst and an anchoring compound, not only makes the composite nanofiltration membrane have high flux characteristics, but also can ensure a high retention rate of divalent inorganic salt ions; and, the catalytic intermediate layer can also improve the reaction activity of interfacial polymerization monomers, broaden the scope of monomer use, so that low-activity monomers also have higher water flux and retention rate; at the same time, reduce the disordered diffusion of reactants at the phase interface, and enhance the self-inhibition of the interfacial polymerization reaction.
[0167] It can be seen from Examples 1 to 10 that the permeation flux of the composite nanofiltration membrane is 16.1 to 27.4 Lm -2 h -1 bar -1 The sodium sulfate retention rate is 90-97%, and even if a low-activity monomer is used, the retention rate is above 90%; the average surface roughness is 6-13nm.
[0168] As can be seen from Example 1 and Example 11, the amount of the ZIF-8 metal organic framework material is too much, and the uneven middle layer morphology hinders the orderly progress of the interfacial polymerization process, resulting in uneven structure of the separation layer obtained, decreased separation performance of the composite membrane, and improved surface roughness; As can be seen from Example 1 and Example 12, the aminopyridine catalyst and the aqueous phase monomer are not in a specific ratio, and the excess catalyst exacerbates the instability of the interfacial polymerization process, resulting in uneven structure of the separation layer obtained, decreased separation performance of the composite membrane, and improved surface roughness; As can be seen from Example 1 and Example 13, the aminopyridine carbon quantum dots are replaced with 4-aminopyridine, and because the catalyst loses the anchoring effect of the coating, its disordered diffusion during the interfacial polymerization process increases the instability of the interfacial polymerization process, resulting in decreased separation performance of the obtained composite membrane, and improved surface roughness. As can be seen from Example 1 and Examples 14 and 15, the raw materials of the aminopyridine nanoparticles are not within a specific molar ratio range, and the catalytic effect of the middle layer is not ideal, resulting in poor performance of the obtained composite membrane.
[0169] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that when the aminopyridine carbon quantum dots are replaced with amination carbon quantum dots or pyridine-activated carbon quantum dots, the integrity of the prepared composite membrane separation layer decreases, the inorganic salt retention rate decreases, and the surface roughness increases due to the loss of catalytic activity of the intermediate layer.
[0170] By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that there is no aminopyridine catalyst or anchor compound in the catalytic intermediate layer material, the incomplete catalytic intermediate layer structure cannot catalyze the interfacial polymerization reaction, the sodium sulfate retention rate of the composite nanofiltration membrane is reduced or the flux is reduced, and the roughness is increased.
[0171] It can be seen from the comparison between Example 1 and Comparative Example 5 that there is no catalytic intermediate layer in the composite nanofiltration membrane. Since the interfacial polymerization reaction lacks catalysis, the permeation flux of the composite nanofiltration membrane decreases and the roughness increases.
[0172] By comparing Example 1 with Comparative Example 6, it can be seen that there is no catalytic intermediate layer in the composite nanofiltration membrane, but when the aminopyridine catalyst and the anchor compound are added to the aqueous phase reactants, the disordered diffusion of the catalytic molecules leads to unstable interfacial polymerization reaction, and the permeation flux of the prepared composite nanofiltration membrane is reduced and the roughness is increased.
[0173] In summary, the composite nanofiltration membrane provided by the present invention adopts a catalytic intermediate layer to improve the reaction activity of monomers and broaden the use scope of low-activity monomers. At the same time, fixing the aminopyridine catalyst in the intermediate layer can limit the disordered diffusion of catalytic intermediates, enhance the stability of the phase interface, and improve the self-inhibition of the interfacial polymerization reaction, thereby obtaining a high-flux composite nanofiltration membrane with a uniform active separation layer structure, reducing the resistance of water passing through the separation layer, thereby improving the separation efficiency in the water treatment process; this high-flux, low-energy consumption composite nanofiltration membrane has great application potential in desalination and wastewater treatment, and the preparation method is simple, the reproducibility is good, and it has good universality. Moreover, according to different treatment requirements, the content of the aminopyridine catalyst in the catalytic intermediate layer can be controlled to obtain a composite membrane with different separation performances.
[0174] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite nanofiltration membrane having a catalytic intermediate layer, characterized in that: The composite nanofiltration membrane comprises a supporting layer, a catalytic intermediate layer and an active separation layer arranged in sequence; The material of the catalytic intermediate layer includes an aminopyridine catalyst and an anchor compound; The anchoring compound comprises at least one of polyphenol, polycellulose, polydopamine, polyacrylic acid, polyurethane, polyvinyl alcohol, polylactic acid, metal organic framework material or covalent organic framework material; The aminopyridine catalyst includes nanoparticles containing aminopyridine groups.
2. The composite nanofiltration membrane according to claim 1, characterized in that In parts by weight, the material of the catalytic intermediate layer includes 0.001 to 10 parts of aminopyridine catalyst.
3. The composite nanofiltration membrane according to claim 1, characterized in that The raw materials of the nanoparticles containing aminopyridine groups include 4-aminopyridine and a nanoparticle precursor.
4. The composite nanofiltration membrane according to claim 3, characterized in that: The molar ratio of the nanoparticle precursor to 4-aminopyridine is 1:(1-2).
5. The composite nanofiltration membrane according to claim 1, characterized in that: In parts by weight, the material of the catalytic intermediate layer includes 0.01 to 0.1 parts of the anchor compound.
6. The composite nanofiltration membrane according to claim 1, characterized in that: The material of the active separation layer includes an interfacial polymer formed by a water phase reactant and an oil phase reactant.
7. The composite nanofiltration membrane according to claim 6, characterized in that: The aqueous phase reactants include monomers containing reactive groups.
8. The composite nanofiltration membrane according to claim 7, characterized in that: The functionality of the monomer containing a reactive group is ≥2.
9. The composite nanofiltration membrane according to claim 7, characterized in that: The reactive group includes at least one of an amino group, a hydroxyl group or a sulfonamide group.
10. The composite nanofiltration membrane according to claim 7, characterized in that: The monomer containing reactive groups includes at least one of m-phenylenediamine, piperazine, resorcinol, 3-aminobenzenesulfonamide, polyethyleneimine or triethylenetetramine.
11. The composite nanofiltration membrane according to claim 7, characterized in that: The aqueous phase reactant includes 0.01 to 10 parts by weight of a monomer containing a reactive group.
12. The composite nanofiltration membrane according to claim 7, characterized in that: The mass ratio of the monomer containing reactive groups to the aminopyridine catalyst is (1-10):
1.
13. The composite nanofiltration membrane according to claim 6, characterized in that: The aqueous phase reactant further comprises 0.01 to 15 parts of additives by weight.
14. The composite nanofiltration membrane according to claim 13, characterized in that: The additives include acid binders and / or surfactants.
15. The composite nanofiltration membrane according to claim 6, characterized in that: The oil phase reactant includes an acyl halide compound.
16. The composite nanofiltration membrane according to claim 15, characterized in that: The functionality of the acyl halide compound is ≥2.
17. The composite nanofiltration membrane according to claim 15, characterized in that: The acyl halide compound includes an acyl chloride compound and / or an acyl bromide compound.
18. The composite nanofiltration membrane according to claim 15, characterized in that: The acyl halide compound includes at least one of 1,3,5-benzene trimethylene dicarboxylic acid chloride, 2,6-naphthalene dicarboxylic acid chloride, terephthaloyl dichloride, isophthaloyl dichloride or phthaloyl dichloride.
19. The composite nanofiltration membrane according to claim 15, characterized in that: The oil phase reactant includes 0.01 to 10 parts of acyl halide compound by weight.
20. The composite nanofiltration membrane according to claim 1, characterized in that: The support layer includes a porous support layer.
21. The composite nanofiltration membrane according to claim 1, characterized in that: The support layer includes at least one of a polysulfone support layer, a polyethersulfone support layer, a polyethylene support layer, a polyamide support layer, a polyimide support layer, a polytetrafluoroethylene support layer, a polyvinylidene fluoride support layer, a polyacrylonitrile support layer or a polyetherimide support layer.
22. A method for preparing a composite nanofiltration membrane according to any one of claims 1 to 21, characterized in that: The preparation method comprises: The support layer, the catalytic intermediate layer and the active separation layer are stacked in sequence to obtain the composite nanofiltration membrane.
23. The preparation method according to claim 22, characterized in that: The preparation method of the catalytic intermediate layer comprises: The aminopyridine catalyst and the anchor compound are mixed with a solvent to obtain an anchor coating solution containing the aminopyridine catalyst; the anchor coating solution is coated on the surface of the support layer to obtain the catalytic intermediate layer.
24. The preparation method according to claim 23, characterized in that: The method further comprises the step of washing the support layer before coating the surface of the support layer.
25. The preparation method according to claim 24, characterized in that: The washing solvent includes ethanol and / or water.
26. The preparation method according to claim 23, characterized in that: The coating method includes at least one of dipping, spin coating or spray coating.
27. The preparation method according to claim 26, characterized in that: The immersion time is 20 to 30 hours.
28. The preparation method according to claim 22, characterized in that: The preparation method of the active separation layer comprises: The surface of the catalytic intermediate layer away from the supporting layer is treated in sequence with a water phase reactant solution and an oil phase reactant solution to perform an interfacial polymerization reaction, thereby obtaining the active separation layer.
29. The preparation method according to claim 28, characterized in that: The method of treatment includes impregnation.
30. The preparation method according to claim 28, characterized in that: The time for treating the surface of the catalytic intermediate layer away from the support layer with the aqueous phase reactant solution is 5 to 15 minutes.
31. The preparation method according to claim 28, characterized in that: The time for the oil phase reactant solution to treat the surface of the catalytic intermediate layer away from the support layer is 20 to 40 seconds.
32. The preparation method according to claim 28, characterized in that: After the active separation layer is obtained, solvent soaking treatment and / or heat treatment are also performed.
33. The preparation method according to claim 32, characterized in that: The solvent in the solvent soaking treatment includes at least one of water, hydrochloric acid, sodium hydroxide, n-hexane, ethanol, triethylamine, benzenesulfonic acid, formamide or ethanolamine.
34. The preparation method according to claim 32, characterized in that: The solvent immersion treatment time is 1 to 10 minutes.
35. The preparation method according to claim 32, characterized in that: The temperature of the heat treatment is 40-100°C.
36. The preparation method according to claim 32, characterized in that: The heat treatment time is 1 to 30 minutes.
37. The preparation method according to claim 22, characterized in that: The preparation method comprises the following steps: (1) mixing an aminopyridine catalyst and an anchor compound with a solvent to obtain an anchor coating solution containing an aminopyridine catalyst; coating the anchor coating solution on the surface of the washed support layer to obtain the catalytic intermediate layer; (2) After the surface of the catalytic intermediate layer away from the support layer is impregnated with an aqueous phase reactant solution for 5 to 15 minutes, the surface of the catalytic intermediate layer away from the support layer is impregnated with an oil phase reactant solution for 20 to 40 seconds to perform an interfacial polymerization reaction, and then the mixture is immersed in a solvent for 1 to 10 minutes and treated at 40 to 100° C. for 20 to 40 seconds to obtain the composite nanofiltration membrane.
38. A desalination nanofiltration membrane, characterized in that: The desalination nanofiltration membrane comprises the composite nanofiltration membrane according to any one of claims 1 to 21.
Citation Information
Patent Citations
Method for preparing composite nanofiltration membrane having ultrathin separating layer
CN107837689A
Preparation method of aminated carbon quantum dots
CN110157422A
Method for preparing thin-layer composite film by electrospraying
CN112892225A
Composite nanofiltration membrane, and preparation method and application thereof
CN113856501A